UPAYA PEMERINTAH DESA MEMBANGUN DESA BONAI KECAMATAN BONAI DARUSSALAM KABUPATEN ROKAN HULU TAHUN 2020-2024 - Maysari, Siti; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
Village development efforts are a national goal to create independence and community welfare, making villages the subject of development as mandated by Law No. 6 of 2014 concerning Villages. In Rokan Hulu Regency, one example of this success is seen in Bonai Village, Bonai Darussalam District, which succeeded in improving its status from "very underdeveloped" to "developing" in the 2020-2024 period. This success is inseparable from the active role of the Bonai Village Government in implementing the three main functions of village government According to Ryass Rasyid. The purpose of this study is to describe the process and results of the implementation of development, service, and community empowerment functions by the Bonai Village Government during that period. This study uses a descriptive approach to describe various initiatives and their impacts. The research results show that: the development function has been successful through various physical projects such as road cementing, public facility construction, and active community participation in mutual cooperation. The service function has shown significant improvements in the quality of administration, health services (including COVID-19 response and stunting prevention), and education management (early childhood education and Islamic boarding schools). Meanwhile, the community empowerment function has succeeded in increasing community knowledge through discussions and training (such as village-owned enterprise (Bumdes) governance and computer skills), as well as local economic development with investor support that produces superior products. Overall, the synergy of these three functions has resulted in an increase in the Village Development Index (IDM) of Bonai Village, although the sustainability and optimization of each aspect require further attention. Keywords: Efforts, Building, Village